Determination of the socio-economic factors that affect the sustainable pasture management in Central Anatolia region of Turkey - Cevher C.; Köksal Ö; Ceylan I.C.; Tatlidil H. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
According to the pasture law and regulations, the responsibilities of the farmers on pasture management have increased since 2004. Therefore, the farmers' attitude and behavior in this subject have gained importance on pasture management. The aim of this study is to present the pasture management methods of farmers in the pastures areas where rehabilitation and amelioration process are completed, and to present the factors that affect farmer's behavior on sustainable pasture management. The data used in the study were obtained by a survey among 271 farmers who live in 18 villages of 3 provinces (Ankara, Kayseri and Konya). The chi square, regression analysis and multiple correspondence analysis methods were used in evaluation of the data obtained. The significant variables that come from 40 variables used in the study were subjected to multiple correspondence analyses. As a result of the regression analysis, it is found that there is a significant relationship (p<0.05) between the sustainable use of the pastures and: the educational level of farmers, their living places, the use of fodder seeds that are provided for them, the participation in pasture rehabilitation activities, the utility found on the rehabilitation activity, the sustainability of the increase in fodder quantity obtained from the rehabilitation project, the use of the pastures out of purpose, whether or not the farmers are willing to rent pastures, the complying with the plan of grazing and the willingness to belong to a pasture management union. To define which categories of the variables found statistically significant in regression analysis were effective, a multiple correspondence analysis method was used. As a result of this analysis it was found that there is a significant relationship between the variable groups that comply with the grazing plan, use of fodder crops seeds, declare willingness to participate in pasture management unions and rehabilitation activities and the sustainable pasture management.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)